Assessment of Radiological Hazards Associated with 40K, 232Th and 232U in Water Samples from New Calabar River, Rivers State, Nigeria. - Igbudu, Onukwurumege; Ogan, Abiye Caleb; Amakiri, Arobo Raymond Chinenye (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
An assessment of radiological hazards associated with intake of 40K, 232Th and 232U in river water samples from New Calabar River, Rivers State, Nigeria, was carried out in this study with the aid of Sodium Iodide (NaI) gamma-ray detector. The water samples were collected into sterile plastic containers and treated by adding 16 ml, 1 M HNO3 solution. This helped to reduce pH of water sample to less than 2, and also allowed for secular equilibrium to be established prior to analysis. Results revealed that mean activity concentration of 40K, 232Th and 232U are 62.43±3.26, 4.18±0.24, and 9.37±1.19 Bql-1 respectively while mean total annual effective dose (mSvy-1) in infants (0-1and 1-2)y, children (2-7 and 7-12)y, and adults (12-17 and ˃17)y are (8.45 and 4.448), (2.999 and 2.666), and (5.347 and 3.207) respectively. Mean absorbed dose and annual effective dose equivalent are 9.461±0.802 nGyh-1 and 11.285±0.962 mSv yr-1respectively. Mean annual gonad dose equivalent, radium equivalent and excess lifetime cancer risk are 65.304±5.716 Bql-1; 19.506±1.806 Bql-1 and 39.550±3.343 E-3, respectively. Mean activity concentration of 40K and 232Th are above recommended safe limits of 10.0 and 0.1 Bql-1 respectively, while that of 232U was slightly below 10 Bql-1 recommended safe limit. All radiological hazard indices considered in this study are above the recommended safe limits hence the river water source is radiologically polluted and unsafe for human consumption. Provision of alternative and safe water supplies, as well as further research studies on areas not captured in this study are recommended.